EBUS-TBNA Cytology Specimens are Predictive of Occupational Dust Exposure in Patients With Bilateral Mediastinal and Hilar Lymphadenopathy. Issue 10 (October 2018) - Pattison, Andrew; Cook, Alistair; Singh, Mahendra; Nandakumar, Lakshmy; Ravi Kumar, Aravind; Fielding, David
Abstract : Objectives: The aim of this study was to describe the cytological features of patients with significant occupational dust exposure presenting with benign bilateral mediastinal and hilar lymphadenopathy (BHL). Methods: A retrospective cohort study including patients undergoing EBUS-TBNA for investigation of benign BHL. Patient characteristics, dust exposure history, radiology, and cytology samples from EBUS-TBNA were assessed. Results: EBUS-TBNA cytology in patients with exposure showed a significant increase in the presence of birefringent fibers (60.7% vs 19.2%, P = 0.001) and intracellular carbon pigment (75.0% vs 28.9%, P = 0.001) compared with patients without exposure. The presence of these two features together yielded a sensitivity of 53.6% and a specificity of 88.5%. Conclusion: In patients with BHL and a history of occupational dust exposure, the presence of birefringent fibers and intracellular carbon pigment in EBUS-TBNA cytology samples may assist in a diagnosis of lymphadenopathy due to occupational dust exposure.